Arterial Wall Imaging in Pediatric Stroke. Issue 4 (April 2018) - Dlamini, Nomazulu; Yau, Ivanna; Muthusami, Prakash; Mikulis, David J.; Elbers, Jorina; Slim, Mahmoud; Askalan, Rand; MacGregor, Daune; deVeber, Gabrielle; Shroff, Manohar; Moharir, Mahendranath
Abstract : Background and Purpose—: Arteriopathy is common in childhood arterial ischemic stroke (AIS) and predicts stroke recurrence. Currently available vascular imaging techniques mainly image the arterial lumen rather than the vessel wall and have a limited ability to differentiate among common arteriopathies. We aimed to investigate the value of a magnetic resonance imaging-based technique, namely noninvasive arterial wall imaging (AWI), for distinguishing among arteriopathy subtypes in a consecutive cohort of children presenting with AIS. Methods—: Children with confirmed AIS and magnetic resonance angiography underwent 3-Tesla AWI including T1-weighted 2-dimensional fluid-attenuated inversion recovery fast spin echo sequences pre- and post-gadolinium contrast. AWI characteristics, including wall enhancement, wall thickening, and luminal stenosis, were documented for all. Results—: Twenty-six children with AIS had AWI. Of these, 9 (35%) had AWI enhancement. AWI enhancement was associated with anterior circulation magnetic resonance angiography abnormality and cortical infarction in 8 of 9 (89%) children and normal magnetic resonance angiography with posterior circulation subcortical infarction in 1 (1 of 9; 11%) child. AWI enhancement was not seen in 17 (65%), 10 (59%) of whom had an abnormal magnetic resonance angiography. Distinct patterns of pre- and postcontrast signal abnormality were demonstrated in the vessel wall in the region of interest in children with transient cerebral arteriopathy, arterial dissection, primary central nervous system angiitis, dissecting aneurysm, and cardioembolic stroke. Conclusions—: AWI is a noninvasive, high-resolution magnetic resonance AWI technique, which can be successfully used in children presenting with AIS. Patterns of AWI enhancement are recognizable and associated with specific AIS pathogeneses. Further studies are required to assess the additional diagnostic utility of AWI over routine vascular imaging techniques, in childhood AIS.